THEORY OF CHANGE AND LOGICAL FRAMEWORK: A COMPARATIVE MEASURE FOR MONITORING AND EVALUATION PRACTICES - Hamdy, M Kholis (Social Welfare Study Program, 2019)
Abstract. This article is a brief study of the advantages and disadvantages of Theory of Change (ToC) and the Logical Framework (Log Frame) based on literature; a comparative approach. The later has a long historical stand in the development practices while the former was formed as supposed to answer the shortcomings of the Log Frame. By comparing both strengths and weaknesses, the finding argues that ToC is strongly considered to have a more certain degree of advantages rather than the M&E in view of development agencies especially NGOs in the practice of monitoring and evaluation of development practices. M&E, in particular, gave birth to ToC in pursue of answering the Log Frame’s current shortcoming. ToC has gained positive stand in the realm of international development by addressing at least three main features: participation, flexibility and the dynamic of development deliverance and accountability. Abstrak. Artikel ini adalah studi singkat tentang kelebihan dan kekurangan dari Theory of Change (ToC) dan Logical Framework (Log Frame) berdasarkan literatur; pendekatan komparatif. Yang kedua memiliki pendirian historis yang panjang dalam praktik pembangunan, sementara yang pertama dibentuk untuk menjawab kekurangan Log Frame. Dengan membandingkan kekuatan dan kelemahan, temuan ini berpendapat bahwa ToC secara kuat dianggap memiliki tingkat keuntungan yang lebih pasti daripada M&E dalam pandangan lembaga pembangunan terutama LSM dalam praktik pemantauan dan evaluasi praktik pembangunan. Monitoring & Evaluation secara khusus melahirkan ToC dalam rangka menjawab kekurangan Log Frame saat ini. ToC telah mendapatkan posisi positif di bidang pembangunan internasional dengan mengatasi setidaknya tiga fitur utama: partisipasi, fleksibilitas dan dinamika pembebasan dan akuntabilitas pembangunan.